CCDC39 is required for assembly of inner dynein arms and the dynein regulatory complex and for normal ciliary motility in humans and dogs - Merveille, Anne-Christine; Davis, Erica E; Becker-Heck, Anita; Legendre, Marie; Amirav, Israel; Bataille, Géraldine; Belmont, John; Beydon, Nicole; Billen, Frédéric; Clément, Annick; Clercx, Cécile; Coste, André; et al. (Nature genetics, 2011)
Michel Georges and colleagues identify a founder mutation in CCDC39 associated with primary ciliary dyskinesia in Old English Sheepdogs. They further show that mutations in human CCDC39 cause a similar phenotype and that CCDC39 is required for the assembly of inner dynein arms and the dynein regulatory complex. Primary ciliary dyskinesia (PCD) is an inherited disorder characterized by recurrent infections of the upper and lower respiratory tract, reduced fertility in males and situs inversus in about 50% of affected individuals (Kartagener syndrome). It is caused by motility defects in the respiratory cilia that are responsible for airway clearance, the flagella that propel sperm cells and the nodal monocilia that determine left-right asymmetry 1 . Recessive mutations that cause PCD have been identified in genes encoding components of the outer dynein arms, radial spokes and cytoplasmic pre-assembly factors of axonemal dyneins, but these mutations account for only about 50% of cases of PCD. We exploited the unique properties of dog populations to positionally clone a new PCD gene, CCDC39 . We found that loss-of-function mutations in the human ortholog underlie a substantial fraction of PCD cases with axonemal disorganization and abnormal ciliary beating. Functional analyses indicated that CCDC39 localizes to ciliary axonemes and is essential for assembly of inner dynein arms and the dynein regulatory complex.